Unobservables, Pregnancy Resolutions, and Birth Weight Production Functions in New York City - Grossman, Michael; Joyce, Theodore J. (Journal of Political Economy, 1990)
This paper makes contributions to the estimation of health production functions and the economics of fertility control. We present the first infant health production functions that simultaneously control for self-selection in the resolution of pregnancies as live births or induced abortions and in the use of prenatal medical care services. We also incorporate the decision of a pregnant woman to give birth.